The influence of communication, coordination, and bureaucratic leadership style in the planning, research, and development agency through interpersonal perception on the job satisfaction of regional apparatus employees in the Riau Islands Provincial Government - Ngaliman Ngaliman; Sri Rahima; I Wayan Catrayasa (Goodwood Publishing, 2024)
Purpose: This study analyzes the influence of motivation, organizational commitment, and workload on job satisfaction of regional officials with competency as an intervening variable in the Riau Islands Province Regional Financial and Asset Agency. In 2023, 11,380 files (49.26 %) experienced delays in processing from SPP to SP2D for 3 – 10 days. Research Methodology: A quantitative approach with census sampling of 105 employees was used. Data were collected through questionnaires with a five-point Likert scale and analyzed using PLS-SEM (SmartPLS 4) to assess validity, reliability, and structural relationships. Results: Using primary data from 143 employees, this study found that motivation has no direct significant effect on job satisfaction. In contrast, motivation, commitment, and workload significantly influence competence, highlighting the importance of motivation in improving employee performance. Competence has also been proven to be a significant mediator between motivation, commitment, and workload on job satisfaction. Conclusions: Employee satisfaction is strongly shaped by effective communication and leadership, supported by positive interpersonal perceptions, whereas coordination contributes weakly. Limitations: This study focused only on one government agency with cross-sectional data, limiting generalization and temporal analysis. Contribution: This study highlights the mediating role of interpersonal perception, offering practical insights for strengthening communication and leadership to enhance satisfaction in public institutions.